2021
DOI: 10.1007/s12325-021-01819-2
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastatic Patterns and Survival Predictors Based on Tumor Size in Pancreatic Ductal Adenocarcinoma

Abstract: BACKGROUND: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies. Its larger mass size is widely acknowledged to be associated with increased lymph node (LN) metastatic potential. However, the quantitative relationships between tumor size and LN metastasis or survival remain unclear. Thus, this study aims to quantitatively identify the objective relationship between tumor size and prevalence of LN metastases across primary tumor size spectrums. METHODS: 9,958 resected PDAC patients wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Lymphangiogenesis is well characterized as an essential step in LN metastasis in various cancers ( 37 ). Clinical evidence has shown that a high density of lymphatic vessels in PDAC is associated with increased LN metastasis and decreased OS ( 38 , 39 ). Currently, the universally acknowledged mechanism for lymphangiogenesis mainly focuses on the VEGF-C–mediated lymphatic pathways ( 3 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangiogenesis is well characterized as an essential step in LN metastasis in various cancers ( 37 ). Clinical evidence has shown that a high density of lymphatic vessels in PDAC is associated with increased LN metastasis and decreased OS ( 38 , 39 ). Currently, the universally acknowledged mechanism for lymphangiogenesis mainly focuses on the VEGF-C–mediated lymphatic pathways ( 3 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The peripancreatic regional lymph nodes are frequently involved by disease (8). Larger tumor size (T stage) is widely acknowledged to be associated with increased lymph node metastasis (7,9). Resectable pancreatic cancers are typically in the earliest stages of the disease (stage 1A, 1B or 2A) and any nodal involvement outside the field of disease indicates unresectable disease (6).…”
Section: Discussionmentioning
confidence: 99%
“…Muralidhar et al [ 35 ] reported that lymph-node metastasis was more likely to occur in patients with larger pancreatic tumors at advanced T stages, illustrating the potential correlation between the T stage and lymph-node metastasis. Pu et al [ 10 ] found that the lymph-node metastasis rate reached a plateau of 70%-80% in patients with pancreatic tumors of > 40 mm diameter, and that about 50% of patients with stage-T3 pancreatic carcinoma and lymph-node metastasis were categorized as stage N2. After researching the mode of lymph node metastasis in pancreatic carcinoma patients, Kanda et al [ 11 ] reported that distant lymph-node metastasis was seen only in stage-T3- and -T4 pancreatic carcinoma, with station-16 metastasis observed in 10.7% and 33.3% of cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the positive lymph node count and long-term prognosis after ELD were not improved in patients with stage-T1 and -T2 disease. Radical resection can be achieved with SLD in these patients due to the relatively low lymph-node metastasis rate and absence of distant lymph-node metastasis[ 10 , 11 ], which may explain the limited benefit of ELD in these cases. The clinical value of ELD in patients with stage-T1 and -T2 PHC needs to be analyzed further.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation